The Influence of Taxation Lore, Taxation Socialization and Taxation Sanctions on MSME Assesable Obedience is Moderated by the Quality of Fiscal Services (Survey on UPTD Partners of Revolving Fund Management of Tangerang Regency) - Muhammad Harun Sukarno; Hidayah, Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Purpose of this study is analyze and empirically prove the effect of taxation lore, taxation socialization and taxation sanctions on msme assesable obedience moderated by the quality of fiscal services. The type of research used is descriptive quantitative. The study population is Assesables of Micro, Small and Medium Enterprises who partner with UPTD Revolving Fund Management as many as 299 units. The sampling technique used in this study is non-probability sampling. The method used is convenience sampling with the slovin formula with a sample of 172 respondents / MSME units. In analyzing data using the Structural Equation Model (SEM) test to determine the causal relationship between variables. The results showed that taxation lore has a positive and significant effect on MSME Assesable Obedience, Taxation Socialization has a positive but not significant effect on MSME Assesable Obedience and Taxation Sanctions have a negative and insignificant effect on MSME Assesable Obedience. The Quality of Fiscus Services is able to significantly strengthen the relationship of Taxation Lore to MSME Assesable Obedience, the Quality of Fiscus Services weakens but not significantly the relationship of Taxation Socialization to MSME Assesable Obedience and the Quality of Fiscus Services significantly weakens the relationship between Taxation Sanctions to MSME Assesable Obedience